PERAN MOHAMMAD TOHA PADA PERISTIWA BANDOENG LAOETAN API TAHUN 1945-1946 - Mohammad Luthfi Herlambang; Kurniawati Kurniawati; Sri Martini (Historiography: Journal of Indonesian History and Education, 2021)
In the early days of independence, most cities in Indonesia still did not fully experience independence due to the colonialist's desire to regain control of their power in Indonesia. After the proclamation of independence was read out, the colonialists still wanted to control the remaining territories of their colonies. In various confIicts, one of them is in the city of Bandung, nameIy Bandung Iautan Api. This was initiated when the allied troops arrived in the city of Bandung to form a defense base in the city of Bandung. In this study, the figure to be discussed is Mohammad Toha, he joined the BBRI (Barisan Banteng RepubIik Indonesia) in 1945 by following several battle missions in the city of Bandung from 1945 to 1946. In his resistance, Toha succeeded in completing his mission of detonating a Dutch gunpowder warehouse. in DayeuhkoIot in 1946 which led to the end of the Bandung Lautan Api incident.Pada masa awaI kemerdekaan, sebagian besar kota-kota di Indonesia masih beIum sepenuhnya merasakan kemerdekaan dikarenakan keinginan penjajah untuk kembaIi merebut kekuasaannya di Indonesia. SeteIah dibacakannya prokIamasi kemerdekaan justru membuat para penjajah tetap menginginkan menguasai wiIayah sisa jajahannya. Diberbagai konfIik yang terjadi saIah satunya di kota Bandung yaitu Bandung Iautan Api. HaI ini diawaIi ketika kedatangan tentara sekutu ke kota Bandung untuk membentuk basis pertahanan di kota Bandung. DaIam peneIitian ini tokoh yang akan dibahas yaitu Mohammad Toha, dia bergabung dengan BBRI (Barisan Banteng RepubIik Indonesia) tahun 1945 dengan mengikuti sejumIah misi pertempurannya di kota Bandung dengan kurun waktu 1945 hingga 1946. DaIam perIawanannya Toha berhasiI menyeIesaikan misinya daIam peIedakan gudang mesiu miIik BeIanda di DayeuhkoIot tahun 1946 yang menyebabkan berakhirnya peristiwa Bandung Lautan Api.